Infusion of Magnetic Nanocatalyst to Microwave Propped Synthesis of Bioactive Azaheterocycles - Hadole, Pranali; Shingda, Sampat; Mondal, Aniruddha; Lal, Kundan; Chaudhary, Ratiram G.; Mondal, Sudip (Current Microwave Chemistry, 2023)
Microwave-assisted synthesis is a powerful tool in organic chemistry, providing a rapid and efficient method for the synthesis of bioactive heterocycles. The application of microwaves significantly reduces reaction times and increases percentage yields with high purity of the final product. To make the synthetic protocol greener, the application of the magnetic nanocatalyst is a rapidly growing area of interest nowadays. Magnetic nanocatalyst, with its unique features like magnetic separable facile recovery from the reaction media heterogeneously, makes the overall synthetic strategy cleaner, faster, and cost-effective. Aiming this, in the present review, we will focus on the infusion of Magnetic nanocatalyst to microwave-assisted synthesis of various classes of azaheterocyclic compounds, including pyridines, pyrimidines, quinolines, and benzimidazoles. The synthetic methodologies involved in the preparation of these heterocycles are highlighted, along with their biological activities. Furthermore, in this review, the most recent and advanced strategies to incorporate nanocatalysts in the microwave-assisted synthesis of natural products containing azaheterocyclic moieties in drug discovery programs are elucidated in detail, along with the incoming future scope and challenges.
Keywords: Microwave-assisted